Practices and modes of modern urban spacevision - R. D. Fanagey (Ukrainian Cultural Studies, 2019)
The article is devoted to the cultural analysis of the influence of the theory of postfordism, which considers post-Fordist production with post-industrial technology as the basis of industrial reproduction at the global level and the reproduction of capitalist social relations after the crisis of the Fordist mode of production and consumption. The abstract social space of the city is studied, which is formed by abstraction of labor and fetishization of things at the level of practice and the formation of a visually geometric representation of space with sign power repressive in relation to reality. The basis of the concept of sociality as the basis of a unified theory of space was developed by the French philosopher and sociologist A. Lefebvre and further developed by American social geography and urban studies, in particular in the works of D. Harvey, E. Soggy, D. Gottdiener and others. The followers of Lefebvre (apart from those important are F. Jameson’s influence) refer in particular to the interdisciplinary trend of post-Fordism, within which postmodernism is considered in connection with the post-Fordist regime of accumulation (a concept developed by the Marxist regulatory school). S. Lesch focuses on the cultural mode of signaling. Likewise, D. Hartmann considers the influence of postmodernism on the post-Fordist regime of capitalism. Paolo True and Pascal Gillen consider within the limits of post-Fordism the existence in modern conditions of the plural. V. Martyanov examines the links between post-Fordism and the post-industrial / information society conceptualized by D. Bell, E. Toffler, M. Castels and others. The article deals with the reconstruction of the theory of social space and post-Fordism and outlines the social transformations of the twentieth century. In essence, it was a search for confirmation that the accumulation mode produces and reproduces social space. Architecture and urban space have become an important structural link through which to consider this connection and justify the invariance of the basic mode of accumulation through the reproduction of abstract social space and vice versa. The analysis of the discourse around the urban abstract space associated with the identity of the bourgeois class and the need for the formation of a hierarchized homogeneous spatial texture of production is carried out. As well as post-Fordist globalization and post-industrialization, which led to a change in the function and structure of the city with the main role of the post-modernist regime of signification as the logic of late capitalism in the context of programmed consumption.